A Textual Evaluation of Manhaji by Joko Nursiyo: Insights from Al-Ghali and Abdul Hamid Abdullah’s Standards - Fauzan Fitra Syahrizal; Syofyan Hadi; Asrina Asrina (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2025)
This study aims to analyze the content of the "Manhaji" book by Joko Nursiyo, widely used in the instruction of Arabic grammar and morphology (nahwu and sharaf), particularly among non-Arab learners such as students from Indonesia, Malaysia, and Thailand. The book is well-known for its methodological approach that combines practical application, memorization, and syntactic analysis using Qur’anic verses and classical texts. It has been implemented both in Indonesia and Egypt, especially among students preparing for higher Islamic studies. The research adopts a qualitative descriptive approach using content analysis methodology, based on the theoretical framework of good textbook standards as outlined by Nasser Abdullah Al-Ghaly and Abdul Hamid Abdullah. The focus is on three core foundations: cultural (thaqāfī), psychological (nafsī), and linguistic (lughawī) principles. The findings reveal that culturally, the "Manhaji" book successfully integrates strong Islamic values aligned with the background of Muslim learners. However, it lacks representation of broader contemporary Arab culture, which is essential for comprehensive Arabic language acquisition. Psychologically, the book offers practical exercises and simplified explanations that aid student understanding, though it still lacks sufficient attention to gradual learning stages and age-appropriate content. Linguistically, while the book excels in providing Qur’anic examples and syntactic exercises, it falls short in the systematic progression of vocabulary and diversity of language registers. This study recommends future development of nahwu-sharaf textbooks that strike a balanced integration of religious values, learner-centered psychological approaches, and modern linguistic principles to meet the evolving needs of non-native Arabic speakers.